Soil water content and temporal stability in an arid area with natural and planted grasslands. Issue 25 (19th October 2018) - Huang, Ze; Miao, Hai‐Tao; Liu, Yu; Tian, Fu‐Ping; He, Honghua; Shen, Weibo; López‐Vicente, Manuel; Wu, Gao‐Lin
Abstract: Soil water content (SWC) is a key factor for successful vegetation restoration in arid and semiarid regions, and vegetation has significant influences on the spatial patterns and temporal dynamics of SWC. The aim of this study was to investigate the temporal stability of SWC under different restored grasslands in an arid hilly area of Central China. SWC was measured in the 0‐ to 300‐cm soil profile in the natural grassland ( Stipa capillata ) and three typical planted grasslands ( Medicago sativa, Agropyron cristatum, and Caragana korshinskii ) over two growing seasons (from June to October 2015 and 2016) under natural rainfall conditions. The results showed that the mean SWC in the natural grassland was approximately 30% higher than those in the planted grasslands. The SWC consumption of the planted legume grasslands in the deepest soil layers (below 200 cm) was higher than that of the natural grassland, owing to the deep root system of the legumes. Both natural and planted grasslands had low SWC temporal stability in the top soil layers (0–50 cm), whereas more stable conditions were gradually observed with increasing the soil depth. The mean value of the mean relative differences of SWC in natural grassland (ca. 15%) was lower than that in the planted grasslands ( A. cristatum grasslands) and much lower than that in the scrubland, highlighting the stronger temporal stability of SWC in the natural grassland. In conclusion, natural grassland could maintain higher and stable SWC and is recommended to be used for achieving sustainable vegetation restoration in arid and semiarid regions.